Perlindungan Hukum Korban Kekerasan Seksual Di Kota Bekasi Pasca Berlakunya Undang-Undang Tindak Pidana Kekerasan Seksual (Kajian Tahun 2022-2024) - Bita Sari Dewi; Fakhris Lutfianto Hapsoro (Jurnal Riset Multidisiplin Edukasi, 2025)
Legal protection for victims of sexual violence in Bekasi City after the enactment of the Law on Sexual Violence Crimes (UU TPKS) has become a crucial issue in Indonesia's legal system. Prior to UU TPKS, legal protection for victims was weak and inadequate, with regulations focusing more on the rights of perpetrators rather than victims. Therefore, this study aims to answer two main research questions: how legal protection is provided to victims of sexual violence under UU TPKS, and how its implementation is carried out in Bekasi City. This research employs a normative juridical method with a statutory and conceptual approach. The findings indicate that although UU TPKS has strengthened legal protection by granting victims the right to legal assistance, psychosocial recovery, and restitution, its implementation in Bekasi City still faces significant obstacles. These challenges include the lack of regulatory harmonization, weak inter-agency coordination, and limited protection facilities for victims. Therefore, concrete steps are needed, such as improving coordination between institutions, drafting clearer implementing regulations, and enhancing the capacity of law enforcement officers to ensure the effective protection of sexual violence victims